Endophytic bacterium Bacillus subtilis (BERA 71) improves salt tolerance in chickpea plants by regulating the plant defense mechanisms. Issue 1 (1st January 2018) - Abd_Allah, Elsayed Fathi; Alqarawi, Abdulaziz A.; Hashem, Abeer; Radhakrishnan, Ramalingam; Al-Huqail, Asma A.; Al-Otibi, Fatma Olyan Naser; Malik, Jahangir Ahmad; Alharbi, Raedah Ibrahim; Egamberdieva, Dilfuza
ABSTRACT: Plant growth-promoting endophytic bacteria can stimulate the growth, nutrient acquisition, symbiotic performance and stress tolerance of chickpea plants under saline soil conditions. The aim of this study was to investigate the stress-adaptive mechanisms of chickpea plants mediated by Bacillus subtilis (BERA 71) under saline conditions. Inoculation with BERA 71 enhanced plant biomass and the synthesis of photosynthetic pigments and reduced the levels of reactive oxygen species (ROS) and lipid peroxidation in plants under conditions of stress. Furthermore, the activities of ROS-scavenging antioxidant enzymes (superoxide dismutase, peroxidase, catalase and glutathione reductase), the levels of non-enzymatic antioxidants (ascorbic acid and glutathione) and the total phenol content were increased in stressed plants during bacterial association. The bacteria decreased sodium accumulation and enhanced the nitrogen, potassium, calcium and magnesium content in the plants. The suppression of ROS generation and of lipid peroxidation and the accumulation of proline in BERA-71-inoculated plants enhanced the membrane stability under salinity stress and non-stress conditions.